The structure of an irrigation scheme - Holbrook, Gregory Martin (Rhodes University, Faculty of Humanities, Department of Anthropology, 1993)
Faced with problems related to the sustainability and advisability of contemporary irrigation development in Africa, anthropologists have increasingly looked to economic and political explanations for the success or failure of those development schemes. Instead of seeking explanations in these isolated areas, this thesis has argued that irrigation development needs to be understood through relationships within and between politics, economics, social structure and culture. In order to uncover those interactions with regard to the Tyefu Irrigation Scheme in the southern African homeland of Ciskei, reference has been made, firstly, to the mechanisms underlying contemporary state expansion and secondly, to the interaction between external forces, structures and surface forms through time. Anthropological fieldwork techniques have been used to provide detailed descriptions of everyday communications within and between groups associated with the development. Ethnography allows implementation to be conceptualized in terms of the interaction between local level structures and structures associated with the planning and construction of irrigation development itself. When the effect of external forces on the interaction between structures and forms is then taken into account principles emerge that reflect local and historical transformations. These in turn suggest the form of contemporary state expansion in southern Africa, as well as its bearing on daily life on the rural periphery.
Keywords: Tyefu Irrigation Scheme -- South Africa -- Eastern Cape; Agricultural development projects -- South Africa -- Ciskei; Irrigation -- South Africa -- Ciskei; Xhosa (African people) -- Economic conditions; Xhosa (African people) -- Social life and customs